Helping Others, Warming Yourself: Altruistic Behaviors Increase Warmth Feelings of the Ambient Environment - Hu, Tian-Yi; Li, Jingyu; Jia, Huiyuan; Xie, Xiaofei (Frontiers in Psychology, 2016)
Altruistic behaviors typically improve the welfare of the recipient at the cost of the performer’s resources and energy. Do altruistic performers obtain any positive internal reward from altruistic behaviors? We conducted six experiments to explore whether altruistic behaviors could increase performer’s warmth perception of the ambient environment. The first three studies focused on crisis situations. A retrospective field study (Study 1, with Hurricane Sandy) and two laboratory studies (Study 2a and 2b, with an earthquake scenario) found that people who helped others felt warmer of the ambient environment than people who did not. We extended to daily life situations and found that participants who performed helping behaviors in laboratory (either voluntarily in Study 3a or randomly assigned to in Study 3b) and passers-by who donated to a charity (Study 4) reported warmer perception of the ambient environment than those who did not. These findings suggested an immediate internal reward of altruism.